I am trying to find the runtime of:

$T\left(n\right)\:=\:n\:+\:\sum _{i=1}^{n-1}\left(T\left(i\right)\right)$

$T(1)= 1$

What is the way to solve this kind of problems?


1 Answer 1



$$ \cases{ T_n = n +\sum_{i=1}^{n-1}T_i\\ T_{n-1} = n-1 + \sum_{i=1}^{n-2}T_i } $$

subtracting the second from the firts we have

$$ T_n-T_{n-1}=1+T_{n-1} $$


$$ T_n -2T_{n-1}= 1 $$

with solution (it is easy to solve)

$$ T_n = c_02^n+2^n-1 $$

and considering the initial value

$$ T_n = 2^n-1 $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.